2013
DOI: 10.1007/s11764-013-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among long-term survivors of breast, prostate, colorectal, and gynecologic cancers: a gap in survivorship care?

Abstract: Purpose Individuals diagnosed with high survival cancers will often die of cardiovascular disease (CVD) rather than a recurrence of their cancer, yet CVD risk factors may be overlooked during survivorship care. We assess the prevalence of CVD risk factors among long-term cancer survivors and compare results to survey data from the general population in the same geographic region. We also characterize how often at-risk survivors discuss CVD-related health behaviors with their health care providers. Methods Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 34 publications
7
192
3
6
Order By: Relevance
“…Previous studies found no significant difference in the prevalence of hypertension between cancer survivors and non-cancer survivors (Enright et al, 2010),slightly higher prevalence in cancer survivors according to cancer types (Shin et al, 2008;Weaver et al, 2013), or specific treatment methods (Jain et al, 2007;Valentova et al, 2011). Hypertension was the most frequent comorbid condition treated in cancer survivors (Goytia et al, 2009), and there is a widespread need for the management of chronic diseases and related risk factors to reduce the late adverse effects of chemotherapy and radiation (Daher et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies found no significant difference in the prevalence of hypertension between cancer survivors and non-cancer survivors (Enright et al, 2010),slightly higher prevalence in cancer survivors according to cancer types (Shin et al, 2008;Weaver et al, 2013), or specific treatment methods (Jain et al, 2007;Valentova et al, 2011). Hypertension was the most frequent comorbid condition treated in cancer survivors (Goytia et al, 2009), and there is a widespread need for the management of chronic diseases and related risk factors to reduce the late adverse effects of chemotherapy and radiation (Daher et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…19 Other investigators conceptually defined cardiovascular disease risk as the presence of cardiovascular disease risk factors including smoking and having an overweight or obese body mass index. 23,30,31 Changes in heart function, including decreases in left ventricular ejection fraction, presence of serum biomarkers, and changes in cardiorespiratory fitness, also comprised the conceptual …”
Section: Conceptual Definitionsmentioning
confidence: 99%
“…3,[32][33][34][35][36][37][38][39][40] Four studies used self-reported history of cardiovascular diseases or cardiovascular disease risk factors as an operational definition. 23,28,30,31 Attributes According to Rodgers, attributes provide a "real definition as opposed to a nominal or dictionary definition". 12 Attributes are the features that comprise the concept as opposed to the conceptual definition of the concept.…”
Section: Operational Definitionmentioning
confidence: 99%
“…73 There also is a disparity in noncancer mortality (especially cardiovascular disease) among cancer survivors, with African American survivors reporting significantly more cardiovascular disease risk factors (except smoking). 74 Patients with more severe comorbidities also are less likely to undergo colonoscopy screening. 75,76 One very clear source of racial disparity in cancer survival is the differential burden of comorbid chronic medical conditions experienced by African American individuals.…”
Section: Health Care Factors: Quality and Intensity Of Treatmentmentioning
confidence: 99%